Augustine and Pelagius View on Salvation: Salvation by Grace or Works - Kasingku, Juwinner Dedy (Klabat Theological Review, 2021)
Salvation is a crucial part of a Christian’s life. There are several interpretations according to the term of salvation. We are saved by grace and through faith and our salvation is the gift from God, but the questions arise, if salvation is given by God, why do we have to obey the law of God, is it taking apart for our salvation? What do both Augustine and Pelagius view about salvation? Are they have the same perspective about salvation or not? How does the Seventh-day Adventist outlook about salvation and how the bible says according to this issue? There are at least 2 arguments that arise related to this discussion. The argument from Pelagius that human effort affects salvation while Augustine’s argument states that there is no part at all for humans to get salvation but an absolute gift from God. The purpose of the research paper is to know about salvation that is given by God. Besides that, to compare what is salvation according to Augustine and Pelagius with the Seventh-day Adventist beliefs which is suitable with our doctrine or not. Salvation is an absolute gift of God, so the good deeds produced by human beings are an expression of gratitude for the salvation that God has given. Keywords: salvation, grace, faith, good deeds.